2020
DOI: 10.1002/lno.11671
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous vehicle surveys indicate that flow reversals retain juvenile fishes in a highly advective high‐latitude ecosystem

Abstract: Summer surveys of the Chukchi Sea indicate that high densities of age‐0 gadid fishes, historically Arctic cod (Boreogadus saida) but recently also walleye pollock (Gadus chalcogrammus), dominate the pelagic fish community. Adults are comparatively scarce, suggesting that either overwinter survivorship of age‐0 gadids is low, or that they emigrate to other areas of the Pacific Arctic. To examine population movement, we conducted repeat acoustic surveys with saildrone autonomous surface vehicles equipped with ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 61 publications
(138 reference statements)
0
13
0
Order By: Relevance
“…Surveys during the recent period of extreme warming (2017-2020) indicate that while the distributions of the other pelagic forage fishes have not significantly changed, pollock abundance in the Pacific Arctic has substantially increased (Figure 2). In the eastern Chukchi Sea, juvenile pollock were widespread and highly abundant in 2017 and 2019 and found in comparable densities to Arctic species (Levine et al, 2021; recent work of author Levine). In the Russian sector, surveys in 2018 and 2019 found a significant increase in both juvenile and adult pollock north of the Chukotka Peninsula (Orlov et al, 2020).…”
Section: Walleye Pollockmentioning
confidence: 94%
“…Surveys during the recent period of extreme warming (2017-2020) indicate that while the distributions of the other pelagic forage fishes have not significantly changed, pollock abundance in the Pacific Arctic has substantially increased (Figure 2). In the eastern Chukchi Sea, juvenile pollock were widespread and highly abundant in 2017 and 2019 and found in comparable densities to Arctic species (Levine et al, 2021; recent work of author Levine). In the Russian sector, surveys in 2018 and 2019 found a significant increase in both juvenile and adult pollock north of the Chukotka Peninsula (Orlov et al, 2020).…”
Section: Walleye Pollockmentioning
confidence: 94%
“…The USVs were equipped with a Simrad WBT mini split-beam echosounder equipped with an ES38-18/200-18CR transducer (18 • split-beam 38 kHz and 18 • single beam 200 kHz) gimbal mounted on the keel at a depth of 1.9 m (De Robertis et al, 2019;Levine et al, 2021). The echosounders continuously transmitted 0.512 ms narrowband signals every 3 sec.…”
Section: Usv Surveymentioning
confidence: 99%
“…Thus, the development of reliable methods to convert acoustic measurements to species and size without trawling has the potential to transform the use of echosounderequipped USVs. More widespread use of frequency response (Korneliussen, 2018), target-strength measurements (Levine et al, 2021), broadband measurements (Bassett et al, 2017), resonance scattering (Stanton et al, 2012), and application of machine learning (Brautaset et al, 2020;Proud et al, 2020), may ultimately result in better characterization of acoustic targets. Sampling methods that can be adapted to USVs such as small cameras (Fernandes et al, 2016), and environmental DNA samplers (Yamahara et al, 2019;Berger et al, 2020) may prove valuable.…”
Section: Future Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some in situ salinity observations might not be close enough to the surface and often yield large biases when validating L-band radiometric SSS, which are representative of the first top centimeter. Recently, Saildrone, Inc. uncrewed surface vehicles (USVs) have been widely deployed to make near-surface measurements in the Bering Sea, Chukchi Sea and Arctic Ocean [37,38]. The authors in [39] analyzed saildrone data in 2019 and the simultaneous remote sensing salinity products and concluded that many of the mesoscalesubmesoscale variability were captured.…”
Section: Introductionmentioning
confidence: 99%